Enhancement of Growth, Antioxidant Activity, and Immunity in Nile Tilapia (Oreochromis niloticus) Through Recombinant Bacillus subtilis Expressing L-Gulonolactone Oxidase - Jirawadee Kaewda; Surintorn Boonanuntanasarn; Papungkorn Sangsawad; Pimpisut Manassila; Chatsirin Nakharuthai (Antioxidants)
Due to its lack of the L-gulonolactone oxidase (GULO) enzyme, Nile tilapia is unable to synthesize vitamin C; thus, it requires an adequate level of exogenous vitamin C in its diet. To enhance antioxidant properties and vitamin C-related effects, we employed recombinant technology to integrate the GULO-encoding gene into the Bacillus subtilis chromosome. In this study, fish were divided into four groups: those fed with a basal diet (CON), a basal diet + vitamin C (VC), a basal diet + wild-type B. subtilis (BS), and a basal diet + recombinant B. subtilis (BS+GULO). After 90 days of the feeding trial, the BS+GULO groups showed the highest improvements in final weight, weight gain, specific growth rate, average daily gain, and relative growth rate. The VC, BS, and BS+GULO groups exhibited increased total immunoglobulin and lysozyme activity; however, only the VC and BS+GULO groups showed elevated alternative complement 50 levels, phagocytic activity and improved antioxidant parameters compared to the control. HPLC and qRT-PCR analyses revealed elevated serum vitamin C and intestinal GULO mRNA levels in the BS+GULO group. A challenge test showed increased pro-inflammatory gene expression and immune response against S. agalactiae in the BS+GULO group, indicating improved antagonistic activity over wild-type B. subtilis.